A multilevel cross-lagged structural equation analysis for reciprocal relationship between social capital and health. (October 2015) - Yu, Ge; Sessions, John G.; Fu, Yu; Wall, Martin
Abstract: We investigated the reciprocal relationship between individual social capital and perceived mental and physical health in the UK. Using data from the British Household Panel Survey from 1991 to 2008, we fitted cross-lagged structural equation models that include three indicators of social capital vis. social participation, social network, and loneliness. Given that multiple measurement points (level 1) are nested within individuals (level 2), we also applied a multilevel model to allow for residual variation in the outcomes at the occasion and individual levels. Controlling for gender, age, employment status, educational attainment, marital status, household wealth, and region, our analyses suggest that social participation predicts subsequent change in perceived mental health, and vice versa. However, whilst loneliness is found to be significantly related to perceived mental and physical health, reciprocal causality is not found for perceived mental health. Furthermore, we find evidence for reverse effects with both perceived mental and physical health appearing to be the dominant causal factor with respect to the prospective level of social network. Our findings thus shed further light on the importance of social participation and social inclusion in health promotion and aid the development of more effective public health policies in the UK. Highlights: A reciprocal relationship exists between social capital and perceived health status. Social participation predicts subsequent change in mental health and vice versa. Positive perceived wellbeing helps individuals to develop a good support network. Loneliness is significantly related to perceived mental and physical health.